Criteria Development for Affordable Housing in the United Arab Emirates (UAE) - Abuhalimeh, Mohammad Said Jamal (2022)
A Master of Science thesis in Construction Management by Mohammad Said Jamal Abuhalimeh entitled, “Criteria Development for Affordable Housing in the United Arab Emirates (UAE)”, submitted in May 2022. Thesis advisor is Dr. Salwa Beheiry. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).